Struktur Komunitas Ikan Kepe-Kepe Di Daerah Terumbu Karang Pantai Liang Pulau Bunaken Sulawesi Utara - Youdy Joseph Hendrik Gumolili; Maykel A.J. Karauwan; Jeanlly A Solang (PolimdoSains, 2022)
This research was carried out in the coral reef Liang Beach area of Bunaken Island in July 31st 2021 by using the visual cencus method on 5 meters depth. The result of the research showed that there were about 12 species of indicator fish Chaetodontidae are found in the coral reefarea.